2018
DOI: 10.15406/ghoa.2018.09.00331
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of ultrasonography in comparison with colonoscopy for diagnosing of ulcerative colitis

Abstract: Aim: To evaluate diagnostic accuracy of ultrasonography in comparison with colonoscopy as gold standard for diagnosing of ulcerative colitis (UC). Method: In this prospective study, 114 participants who attended in Ahvaz Imam Hospital during March 2014 to February 2015 included. The participants divided into 2 groups: group A as 64 UC patients (flare or new case) and 50 participants as control group who attend for colorectal cancer screening or evaluation of rectorrhagia. All of the participants obtained a Tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
(39 reference statements)
0
1
1
Order By: Relevance
“…On the other side, the results of the current work disagree with Hajiani et al [17] who found that colonic mural thickness among new cases of ulcerative colitis was significantly more than cases who diagnosed as UC flare up and concluded that ultrasonography is not an ideal tool for evaluation of UC patients because its results could be affected by several factors such as body mass index [BMI] and region of involvement. Different phases of the disease included in their study and current work could explain this controversy.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…On the other side, the results of the current work disagree with Hajiani et al [17] who found that colonic mural thickness among new cases of ulcerative colitis was significantly more than cases who diagnosed as UC flare up and concluded that ultrasonography is not an ideal tool for evaluation of UC patients because its results could be affected by several factors such as body mass index [BMI] and region of involvement. Different phases of the disease included in their study and current work could explain this controversy.…”
Section: Discussioncontrasting
confidence: 99%
“…Oral administration of agents such as polyethylene glycol may improve image quality and diagnostic accuracy [7] . BUS for IBD often requires high frequency [5][6][7][8][9][10][11][12][13][14][15][16][17] linear array probes to increase the resolution and to allow adequate assessment of the intestinal wall [8] . Doppler assessment provides additional vascular information and may assist in differentiating predominantly inflammatory from fibrostenotic lesions.…”
Section: Introductionmentioning
confidence: 99%